Definición de un método de caracterización que permita identificar de manera clara los efectos de la formulación de pasta y el calentamiento en la formación de “núcleo negro” mediante la aplicación de herramientas estadísticas. (2023)
This document presents, as its main objective, the definition of a paste characterization method that differentiates its formulation in the formation of the "black core" or, as the literature also refers to this phenomenon, "black heart" in ceramic coatings through of statistical tools for Colcerámica S.A.S in its plant located in Madrid Cundinamarca, which to date has a qualitative definition method by levels which are granted through observation by operators comparing an established board with the ceramic pieces to be evaluated .